ANTECEDENTS INNOVATION CAPABILITY AND CONSEQUENCES IT PERFORMANCE IN THE KERANGGAN VILLAGE TOURISM - Juliana Juliana; Rudy Pramono; Ira B Hubner; Nova Bernedeta Sitorus; Amelda Pramezwary; Sandra Maleachi; Agus Purwanto (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Through the mediation of innovative capability, this study intends to determine the degree and direction of the influence of knowledge management and work environment on the performance of Pokdarwis in the village of Kerangan. Quantitative research was used in this study. In this study, the population and sample were 35 persons in the village of Keranggan who were aware of tourism. Questionnaire-based data collection methods. PLS-SEM is used in the analysis tool. The findings show that the ability to innovate has a strong mediating effect on the relationship between knowledge management and performance, as well as the relationship between performance and the work environment. With the addition of innovation capability, the impact of total knowledge management on performance and the work environment on performance will grow. Pokdarwis performance is influenced by knowledge management and the work environment. This last goal can be realized by a modern management approach that promotes long-term village development activities, as evidenced by increased production, the development of a large base of devoted tourists, and long-term improvements. One type of change necessitates enhancing organizational competence by providing additional dynamic capacities such as the ability to innovate, expand managerial expertise, and create a positive work environment where good performance can be achieved and maintained. village tourism, innovation capability, work environment, knowledge management